2020
DOI: 10.3390/educsci10110316
|View full text |Cite
|
Sign up to set email alerts
|

AR-LabOr: Design and Assessment of an Augmented Reality Application for Lab Orientation

Abstract: Lab orientation is a vital part of learning for new students entering the university, as it provides the students with all the necessary and important information about the lab. The current orientation is manual, tedious, suffers from logistical constraints, lacks engagement, and provides no way to assess that outcomes have been achieved. This is also supported by the results of a student survey which revealed students’ dissatisfaction with current process of orientation. This study presents the design and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 64 publications
0
9
0
1
Order By: Relevance
“…The use of AR in education has been shown to successfully inspire students to study. As an example, a study by [14] demonstrated how AR can be used to support, empower, and assist students, resulting in a more rapid adaptation to the laboratory setting. Students can see the object clearly with the assistance of AR, which helps them gain a better understanding of the lab equipment.…”
Section: B Enhancing Learning Using Armentioning
confidence: 99%
“…The use of AR in education has been shown to successfully inspire students to study. As an example, a study by [14] demonstrated how AR can be used to support, empower, and assist students, resulting in a more rapid adaptation to the laboratory setting. Students can see the object clearly with the assistance of AR, which helps them gain a better understanding of the lab equipment.…”
Section: B Enhancing Learning Using Armentioning
confidence: 99%
“…However, the user cannot make direct changes to the virtual material. 25,34 Applications such as VoxelCO and Fologram enable designers to interact in real-time with their designs and evaluate and reconfigure them on the spot. In this way, they augment the spatial and perceptual skills of the users while fostering creativity and experimentation.…”
Section: Ar Software Used In Architecturementioning
confidence: 99%
“…For new students involved for the first time in research, conducting a lab orientation is an essential step of learning since it offers the students the required and essential information about the lab and hazardous material [35], especially when dealing with prepreg waste. The conducted lab orientation involved a hands-on practice where students attended a lab session led by a safety engineer taking the students for a lab tour to educate them about health and safety issues and rules, demonstrating essential information about lab equipment that would be used in research as well as addressing health concerns and potential risks when handling the prepreg waste pertaining to the material specifications.…”
Section: Safety Is a Prioritymentioning
confidence: 99%